Right to information regime in India: A critical appraisal - Chadah, Sapna (2006)
The right to information has been recognised as an important democratic privilege and one of the essential requirements of good governance. The information regime has dawned on Indian scene after a considerable period of popular aspiration. The Right to information Act of 2005 empowers the citizens to seek information and correspondingly makes it mandatory for the public authorities to disseminate information for better governance and accountability. Besides transparency and opennes the new legislation shall be an instrument to prevent misuse of public power and funds. Here is a discussion on various distinctive and significant features of the Act along with an elucidation on its institutional framework. The author puts forth major concern regarding candour in its implementation and effectiveness in execution. - Reproduced.
Keywords: Right to information - India; Right to information